2007
DOI: 10.1360/yc-007-1131
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a SSR linkage map and mapping of quantitative trait loci (QTL) for leaf angle and leaf orientation with an elite maize hybrid

Abstract: Maize (Zea mays L.) breeders have begun selecting for more compact plants for higher density planting in order to increase yield per unit area. Leaf angle and leaf orientation are very important traits affecting maize plant type (compactness). In this study, a genetic linkage map containing 138 simple sequence repeat (SSR) markers was constructed based on a mapping population consisting of 500 F2 individuals from the cross between inbred lines Ye478 and Dan340. This SSR linkage map spans a total of 1 394.9 cM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 21 publications
1
31
1
Order By: Relevance
“…However, the genetic mechanisms of leaf angle and leaf space were not well known. Only a few studies for the QTL detection for leaf angle and leaf space in maize have been published (Mickelson et al 2002;Yu et al 2006;Lu et al 2007;Ku et al 2010;Zhang et al 2010;Tian et al 2011;Ku et al 2012;Zhu et al 2013;Zhang et al 2014). Moreover, the detection in one generation and single environment did not result in consistent QTLs (Boer et al 2007;Peng et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the genetic mechanisms of leaf angle and leaf space were not well known. Only a few studies for the QTL detection for leaf angle and leaf space in maize have been published (Mickelson et al 2002;Yu et al 2006;Lu et al 2007;Ku et al 2010;Zhang et al 2010;Tian et al 2011;Ku et al 2012;Zhu et al 2013;Zhang et al 2014). Moreover, the detection in one generation and single environment did not result in consistent QTLs (Boer et al 2007;Peng et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al (2006) detected nine QTLs for LA on chromosomes 1, 2, 3, 8, 9 and 10 in two F 2:3 populations derived from H21 9 Mo17 and Zi330 9 K36. Lu et al (2007) detected six QTLs for LA in a F 2:3 family derived from the cross Ye478 9 Dan340, two of which located on chromosomes 1 and 3 explaining 10.8 and 11.2 % of phenotypic variation, respectively. Ku et al (2010) identified three QTLs for LA on chromosomes 1, 2 and 5 with the contribution to phenotypic variation ranging from 7.3 to 20.4 % in a F 2:3 population derived from Yu82 9 Mo17.…”
Section: Introductionmentioning
confidence: 97%
“…For the traits related to plant architecture, PH and EH have been frequently studied (Kraja and Dudley, 2000;Sibov et al, 2003;Lima et al, 2006;Malosetti et al, 2008;Bai et al, 2010), and a large number of QTLs were found to be located in different chromosomal regions. There are also many reports on QTL identification of the LN trait (Jiang et al, 1999;Lima et al, 2006;Tang et al, 2007;Wang et al, 2008), and several studies have been performed on the LA and LO traits (Mickelson et al, 2002;Lu et al, 2007;Ku et al, 2010). Therefore, QTL mapping of traits associated with plant architecture is very significant in maize.…”
Section: Introductionmentioning
confidence: 99%
“…These loci were detected in the BLSB resistance research, which may be attributed to the theory that they affect maize resistance to different disease via the same regulation mechanism such as the Programmed Cell Death and cell-wall thickening, and their specific was of involvements in the maize resistance can be further identified by physiology and biochemistry researches. The particular cases are as follows: the previous studies indicated that bnlg1909 involved in maize From the prospect of loci distribution in chromosomes, loci were detected in all the chromosomes except photosynthesis via regulating the synthesis of chlorophyll a and b [27]; bnlg1017 involved in construction of maize plant type by affecting leaf angle, leaf direction, plant height and height of ear [28], [29]; bnlg1525 involved in drought tolerance [30]. The possible reason for their involvements in BLSB resistance might be as follows: bnlg1909 improved the efficiency of photosynthesis to provide energy for disease resistance [27]; bnlg1017 reduced the infection probability via regulating the angle to make it difficult for germs to invade sheath [31], this may be attributed to the phytopathology theory that BLSB germ infect the plant by invading the sheath initially, the it elevated the ear height to reduce the possibility of ear infection to reduce the effect on maize quality; bnlg1525 involved in the abiotic stress [25], the mechanism may be that according to the physiology and biochemistry researches for drought tolerance, osmotic pressure adjustments, including cell-wall thickening, were involved in the drought tolerance, and the BLSB infection also causes dehydration and degreasing, thus those loci involved in drought tolerance may get involved in maize resistance to BLSB via these methods.…”
Section: Discussionmentioning
confidence: 99%